Tamanho de partícula da silagem de milho na produção e comportamento ingestivo de bovinos leiteiros - Monteiro Filha, Ede Gambini (2007)
With the purpose of evaluating the reduction of particle size in corn silages, 16 dairy cows were used in eight 2 x 2 latin squeres. The factors used for the making of blocks were as follows: labor order and milk production two days before the beginning of the pré-experimental period. The experimental treatments consisted of corn silage offred as such and the same silage with reduced particle size for feeding the animals. The animals fed smaller size of silage particles showed higher intake of dry matter, less time of chewing/kg of ingested dry matter and higher milk production. The reduction of particle size did not affect milk percental composition. The reduction of particle size in corn silage should be reevaluated in most brasilian dairy farms, due to increase of production, such as found in the present study.